2019
DOI: 10.1016/j.semcancer.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation of K-Ras in pancreatic cancer and opportunities for therapeutic intervention

Abstract: The Ras family of GTPases is involved in cell proliferation, cell survival, and angiogenesis. It is upregulated in several cancers, including pancreatic cancer (PC) and leads to uncontrolled growth and aggressiveness. PC is well known to be a lethal disease with poor prognosis, plagued by limited therapeutic modalities. MicroRNAs (miRNAs), which are short non-coding RNA molecules, have recently emerged as regulators of signaling networks and have shown potential to target pathway components for therapeutic use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 83 publications
(128 reference statements)
1
40
0
Order By: Relevance
“…Pancreatic cancer (PC) is very aggressive cancer with a poor prognosis, and, as mentioned above, a KRAS mutation is frequently observed in PC 41,43 . The downregulation of MIR143‐3p results in the activation of KRAS signaling networks, which implies an association between MIR143‐3p and RAS in PC cells 41 .…”
Section: The Role Of Mir143‐3p On Rat Sarcoma Signaling Network In Vmentioning
confidence: 98%
See 2 more Smart Citations
“…Pancreatic cancer (PC) is very aggressive cancer with a poor prognosis, and, as mentioned above, a KRAS mutation is frequently observed in PC 41,43 . The downregulation of MIR143‐3p results in the activation of KRAS signaling networks, which implies an association between MIR143‐3p and RAS in PC cells 41 .…”
Section: The Role Of Mir143‐3p On Rat Sarcoma Signaling Network In Vmentioning
confidence: 98%
“…Regarding RAS signaling networks, MIR143‐3p exerts its anti–tumor effects in various human cancers by targeting RAS and its effector signaling genes, such as AKT and ERK 12,40‐42 (Figure 2, Table 1). MAPK/ERK pathways and PI3K/AKT pathways are critical pathways for the survival and proliferation of cancer cells.…”
Section: The Role Of Mir143‐3p On Rat Sarcoma Signaling Network In Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic failure and poor survival in BCa are attributed to its hyperproliferation and early metastasis . MicroRNAs (miRNA) are small, noncoding RNA molecules that have been reported to play important roles in BCa carcinogenesis by influencing multiple cellular processes, including proliferation, metastasis, radiation sensitivity and chemo‐sensitivity . miRNAs can negatively regulate gene expression through a variety of mechanisms, acting as tumor suppressors or oncogenes …”
Section: Introductionmentioning
confidence: 99%
“…2 MicroRNAs (miRNA) are small, noncoding RNA molecules that have been reported to play important roles in BCa carcinogenesis by influencing multiple cellular processes, including proliferation, metastasis, radiation sensitivity and chemo-sensitivity. [3][4][5] miR-NAs can negatively regulate gene expression through a variety of mechanisms, acting as tumor suppressors or oncogenes. [6][7][8] In the present study, we demonstrated for the first time that miR-4324 was significantly downregulated in BCa, and miR-4324 suppressed important traits in BCa cells, including cell proliferation, metastasis and chemo-resistance.…”
Section: Introductionmentioning
confidence: 99%